Destruction of Toluene by the Combination of High Frequency Discharge Electrodeless Lamp and Manganese Oxide-Impregnated Granular Activated Carbon Catalyst - Jianhui Xu; Chaolin Li; Qian Zhang; Di He; Peng Liu; Yong Ren (International Journal of Photoenergy)
The destruction of low concentration of toluene (0–30 ppm) has been studied under the UV/photogenerated O3/MnO2-impregnated granular activated carbon (MnO2-impregnated GAC) process by the combination of self-made high frequency discharge electrodeless lamp (HFDEL) with MnO2-impregnated GAC catalyst. Experimental results showed that the initial toluene concentration can strongly affect the concentration of photogenerated O3 from HFDEL and the efficiency and mass rate of destruction of toluene via HFDEL/MnO2-impregnated GAC system. Active oxygen and hydroxyl radicals generated from HFDEL/MnO2-impregnated GAC system played a key role in the decomposition of toluene process and the intermediates formed by photolysis are more prone to be mineralized by the subsequent MnO2-impregnated GAC catalyst compared to the original toluene, resulting in synergistic mineralization of toluene by HFDEL/MnO2-impregnated GAC system. The role of MnO2-impregnated GAC catalyst is not only to eliminate the residual O3 completely but also to enhance the decomposition and mineralization of toluene.